Thermodynamic Hadron-Quark Phase Transition of Chiral Nuclear Matter at High Temperature - Nguyen, Tuan Anh (Nuclear Science and Technology, 2017)
Based on the extended Nambu-Jona–Lasinio (NJL) model with the scalar-vector eightpoint interaction [15], we consider what ultimately happens to exact chiral nuclear matter as it is heated. In the realm of very high temperature the fundamental degrees of freedom of the strong interaction, quarks and gluons, come into play and a transition from nuclear matter consisting of confined baryons and mesons to a state with ‘liberated’ quarks and gluons is expected. In this paper, the hadron-quark phase transition occurs above a limited temperature and after the chiral phase transition in the nuclear matter. There is a so-called quarkyonic- like phase, in which the chiral symmetry is restored but the elementary excitation modes are nucleonic at high density, appears just before deconfinement. PACS: 21.65.-f, 21.65.Mn, 11.30.Rd, 12.39.Ba, 25.75.Nq, 68.35.Rh